DYNAMICS OF ORAL HYGIENE INDICATORS AND SALIVITY RATE IN CHILDREN WHO FREQUENTLY HAVE ACUTE RESPIRATORY AND VIRAL INFECTIONS - Pavlenkova, O.S.; Kaskova, L.F. (World of Medicine and Biology, 2021)
Before preventive interventions, the hygienic state in children, often ill, was unsatisfactory and ranged from 2.28±0.23–2.29±0.12 points. A month after the appointment of preventive measures, this indicator improved to satisfactory in children of group 3 and to good in group 4 (who were assigned professional hygiene twice a year, individual hygiene using calcium paste, the use of calcium supplements and those that increase the body's protective properties and amounted to 1.68±0.06 points and 1.5±0.05 points, respectively. 6 months after the first survey, oral hygiene worsened in all children relative to the second survey, but it was better than to take preventive measures. The same picture was observed when determining the hygiene index according to the Green–Vermilion. There is a tendency to improve the rate of salivation after preventive measures.
Keywords: caries; acute respiratory viral infections; hygiene index; salivation rate; children